Algebra
posted by Stacy on .
Let f(x) = 6/x1 and g(x) = 1+3/x. Please fing the composite function.
This is what i got so far.
=f (1+3/x)
=6/x1
= =f (1+3/x)
= 6/ [1+3/x  1]
How do I get the composite?

The definition of a composite function:
f º g (x) means f (g(x) ), which tells you to work out g(x) first, and then fill that answer into f. See
(Broken Link Removed)
In this case,
f(x) = 6/x1 and g(x) = 1+3/x
so
f º g (x)
=f(g(x))
=f(1+3/x)
=6/(1+3/x)1
=6x/(x+3)1
=(6x(x+3))/(x+3)
=(5x3)/(x+3) 
and the composite function would be?
A.(fog)(x)= (2x)
B.(fog)(x) =2/x
C.(fog)(x)=(6/x1)(1+3/x
D.(fog)(x)=1+18/x(x1) 
There is probably a misinterpretation of the parentheses:
f(x) = 6/(x1) and g(x) = 1+3/x
so
f º g (x)
=f(g(x))
=f(+3/x)
=6/(1+3/x1)
=6/(3/x)
=2x
If this is the case, the answer is (A). 
This is what I thought as well. Thanks!